1990
DOI: 10.1007/bf00180667
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation by adenosine and its analogs of potassium-contracted human coronary arteries

Abstract: The present study was an attempt to characterize the adenosine receptor in human coronary arteries, and to establish the dependence of the relaxations mediated by this receptor on a functional endothelium. Human coronary arteries were obtained from organ donors. Adenosine and its analogs (5'-N-ethyl-carboxamido-adenosine, NECA; N6-L-phenylisopropyladenosine, L-PIA; 2-chloroadenosine, CAD), all inhibited the contraction induced by 25 mmol/l KCl in a concentration-dependent manner and the order of potency was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Adenosine is well known to play a vasoregulatory role in human coronary arteries (16,17,62,63). We and others (5,63,67,69) have also previously demonstrated the pivotal role of A 2A ARs in CF regulation.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Adenosine is well known to play a vasoregulatory role in human coronary arteries (16,17,62,63). We and others (5,63,67,69) have also previously demonstrated the pivotal role of A 2A ARs in CF regulation.…”
Section: Discussionsupporting
confidence: 51%
“…The activation of A 1 ARs results in negative chronotropic and ionotropic effects and a decrease in coronary flow (CF) (68), whereas other studies have suggested that the activation of both A 1 ARs or A 3 ARs before ischemia is cardioprotective (6,30). However, adenosine has been shown to play a vasoregulatory role in human coronary arteries (16,17,62,63). It is well established that the activation of A 2A ARs induces positive inotropic effects and that A 2A ARs play a major role in the regulation of CF in ex vivo models (67,69).…”
Section: Sanjani Ms Teng B Krahn T Tilley S Ledent C Mustafa Sjmentioning
confidence: 99%
See 1 more Smart Citation
“…In several human vascular beds, adenosine A 2 receptors mediate vasodilatation in part through endothelium, possibly by releasing NO (Sobrevia et al, 1997;Li et al, 1998) and prostacyclin (Chiang et al, 1994;Donoso et al, 2005). Other studies, however, failed to demonstrate endothelium-dependent responses in the presence of adenosine (Sabouni et al, 1990;Tsai et al, 1996;Kemp and Cocks, 1999). Controversy also exists on the receptor subtype (A 2A or A 2B ) predominating on endothelial cells (Chiang et al, 1994;Iwamoto et al, 1994;Sobrevia et al, 1997;Li et al, 1998;Donoso et al, 2005).…”
mentioning
confidence: 92%
“…A 2 receptors (according to the old nomenclature used by Fredholm et al, 1994) are implicated in many vessels in the hypotensive activity of adenosine, due to the presence of speci®c membrane receptors in many vessels (Rongen et al,described in porcine coronary vasculature (Abebe et al, 1995), while an endothelium-independent A 2 -receptormediated vasodilation is reported in human and guinea-pig coronaries (Sabouni et al, 1990;Vials & Burnstock, 1993). As regards the particular A 2 receptor subtype involved in the adenosine-mediated hypotension, there are di erent indications: A 2a receptors are reported to mediate relaxation of rat aorta and bovine, rat and pig coronary artery (Hutchison et al, 1989;Conti et al, 1993) while A 2b receptors mediate adenosine-induced relaxation in guinea-pig pulmonary artery (Szentmiklosi et al, 1995) and rat mesenteric arterial bed (Rubino et al, 1995).…”
Section: Introductionmentioning
confidence: 99%